2017
DOI: 10.1160/th17-02-0134
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Venous Thromboembolism in Asian Populations: A Systematic Review

Abstract: Introduction Despite a marked recent increase in the number of publications describing the incidence of venous thromboembolism (VTE) in Asia, and especially in mainland China, Hong Kong, Taiwan, Korea, Japan and Singapore, there remains a lack of consensus on the true risks, and trends over time, to inform appropriate clinical practice. The purpose of this systematic review was therefore to examine evidence about the incidence of symptomatic VTE in Asia. Methods Databases were searched for studies from Asia, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
130
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(141 citation statements)
references
References 88 publications
8
130
3
Order By: Relevance
“…In the United States, this translates to 300,000-600,000 cases of VTE per year, and annual incident VTE events are estimated to cost US healthcare more than 7 billion dollars each year [17]. Rates of VTE are lowest in Asian populations and highest in Northern European populations [18,19]. The patient characteristics and risk factors for VTE also vary by region.…”
Section: Venous Thromboembolism Remains a Significant Public Health Cmentioning
confidence: 99%
“…In the United States, this translates to 300,000-600,000 cases of VTE per year, and annual incident VTE events are estimated to cost US healthcare more than 7 billion dollars each year [17]. Rates of VTE are lowest in Asian populations and highest in Northern European populations [18,19]. The patient characteristics and risk factors for VTE also vary by region.…”
Section: Venous Thromboembolism Remains a Significant Public Health Cmentioning
confidence: 99%
“…Finally, NHIRD is a nationwide database of Asian population. Although the prevalence and incidence of VTE were compatible with the systematically reviewed data [31], ethnic difference shall be taken into account while applying the study results into clinical practice globally.…”
Section: Discussionmentioning
confidence: 58%
“…Several reasons could account for the lower VTE rates in our report. Previous studies have shown patients of Asian-descent have lower risk for VTE compared to Western cohorts [9]. Our patients were also younger with fewer comorbidities and they tended to present to the hospital earlier in their course of illness 3, [4] ,8 , which might have led to earlier interventions as re ected in the low median APACHE and SOFA scores on transfer to ICU.…”
Section: Discussionmentioning
confidence: 85%